THE EVOLUTION OF PERFORMANCE TOWARDS THE CHINESE NATIONAL MINORITY EDUCATION POLICY (1978-2016) - Yongtao Gan , Jian Gao ,Surreal Polgampala, Youran Tan, Anli Yang (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The main purpose of the current study is to assess the performance of the Chinese minority education policy (1978-2016).This study collected 272 policies referring to the minority education from 1978 to 2016.Results of the different government departments in terms of goal orientation in the minority education policy on the cooperative showed remarkable stage characteristics; with the country attached great importance to the minority education policy coordination, there is a rapid increase in the level of minority education policy discourse; uneven distribution of the deep-seated reason lies in the system path dependence and power distribution in the national political process. It will analyze the educational consequences under the "New China" policies considering the exploratory work in the minority education policy variables into the Cobb Douglas production function with the intention of exploring the influence of policy for minority education practice performance. Furthermore, this study discusses minority policy orientation of synergistic effect on practice performance in the different government departments.